KARAKTERISASI NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK KULIT BUAH SALAK (Salacca zalacca) SEBAGAI BIOREDUKTOR : UJI WARNA DAN ANALISIS SURFACE PLASMON RESONANCE (SPR) SEBAGAI FUNGSI KONSENTRASI - Athiah Masykuroh; Jiffy Mahardika Koeswara (Akademi Farmasi Yarsi Pontianak, 2026)
Salacca zalacca is a tropical plant whose peel contains secondary metabolites such as flavonoids, tannins, and saponins, which have the potential to act as bioreductant agents in the synthesis of silver nanoparticles (AgNPs). Extraction was carried out by boiling 50 g of Salacca zalacca fruit peel in 500 mL of distilled water at 65°C for 10 minutes. The silver nanoparticles synthesis was performed by mixing the extract at concentrations of 10%, 15%, and 20% with a 0.15 M AgNO₃ solution, then heating the mixture at 70°C for 10 minutes. The results showed a color change of the solution to dark brown; however, no absorbance peak was observed in the wavelength range of 395–515 nm based on UV-Vis spectrophotometric analysis, indicating that AgNPs were not formed.